Dupliumab therapy for alopecia areata: a case series and review of the literature - Jundong Huang; Jia Jian; Tingting Li; Min Li; Kaifu Luo; Sihan Deng; Yan Tang; Fangfen Liu; Zhixiang Zhao; Wei Shi; Ji Li (Taylor & Francis Group, 2024)
AbstractBackground A growing body of research supports the important role of the TH2 axis in alopecia areata (AA). Dupilumab is a humanized monoclonal antibody against IL-4Rα that downregulates TH2 response. Although efficacy has been shown in clinical trials, real-world data on the use of dupilumab in AA patients is limited.Objectives To report on a case series of 10 patients with AA who were treated with dupilumab and provide real-world evidence regarding its efficacy in treating severe AA.Methods In this retrospective single-center study, all AA patients treated with dupilumab treatment were included between May 2022 and October 2023. Clinical outcome measures (Severity of Alopecia Tool, SALT) and adverse events (AEs) were analyzed. In addition, a literature review was conducted to summarize the efficacy of AA with dupilumab and the characteristics of patients previously reported in the literature.Results We identified 10 patients with AA who were or are being treated with dupilumab, with a median (range) treatment duration of 8 (3-15) months. Of these, four patients have high serum immunoglobulin E (IgE) levels (≥200IU/ml). The mean (IQR) pretreatment SALT score was 79% (52-100). Seven of 10 patients achieved at least 50% re-growth. Of those who improved, the mean (IQR) percentage change in SALT score at 3 months and the end of follow-up was 57% (29%-89%) and 95% (68-100), respectively. Notably, seven patients (70%) had white hair regrowth, with the white hair slowly decreasing over time and the proportion of pigmented black hair increasing. Dupilumab was well tolerated by all patients. No adverse events were reported.Conclusions Overall, our research supports dupilumab as another candidate that possesses potential benefits for AA. High levels of IgE may be not prerequisites for dupilumab's successful treatment response.